Education and Focused Ethnography: Use and Conceptualization in Videographic Research - Gil, Nora Liliana González (Journal of Ecohumanism, 2024)
Education opens to new possibilities from the focused ethnographic research, approached in this article, from a look at the use and conceptualization of the modern technique of videography. With the purpose of approaching focused ethnography from the bibliographical review in the field of research, this review article was carried out based on a hermeneutic-qualitative work from the documentary reconstruction, thematization, analysis and conceptualization. The research allowed an approach to the academic production of focused ethnography, and to some ontological and epistemological considerations. Finally, the methodological construction of focused ethnography and the videographic analysis of food practices in the school restaurant showed the relevance of capturing still images of social dynamics for its study. It is concluded that the use of the method is advantageous and makes it possible to understand everyday life, its interrelations and meanings thanks to these modern research techniques.